Determinants of Household Waste Management in Alam Barajo District, Jambi City - Fitria Eka Putri; Muhammad Agung Perdana; Hubaybah; Fajrina Hidayati; Adelina Fitri; Puspita Sari (Lembaga Pengembangan Kinerja Dosen, 2022)
Waste that cannot be recycled and processed properly will be very dangerous for human health and the environment. Based on data from the Environmental Service of Jambi City, garbage in Jambi City reached a total of 465,693,805 kg/day, and the largest waste generation data was in Alam Barajo District where the waste generated was 75,409,004 kg/day. This research is an observational study that uses a quantitative approach with a cross sectional method. The population of Alam Barajo sub-district is 30,786 families. The sampling technique is a disproportionate stratified random sampling technique. Bivariate analysis using thetest Chi-Square, the relationship between the independent variable and the dependent variable, namely knowledge (p = 0.000), attitude (p = 0.122), support from community leaders (p = 0.607), support from health workers (p = 0.227) with waste management household. There is a relationship between knowledge and household waste management in Alam Barajo sub-district and there is no relationship between attitudes, support from community leaders, support from health workers and household waste management.